Examining technology readiness among senior high school teachers: The role of proactive school management - Kadiyono, Anissa Lestari; Wardhani, Admiranti Adhyarizka (Journal of Educational Management and Instruction (JEMIN), 2024)
Teachers play a pivotal role in integrating technology into education. Proactive school management can significantly enhance teachers' ability to utilize technology, making the teaching and learning process more creative, modern, and aligned with contemporary developments. This study investigates the relationship between teachers' technology usage and their technology readiness, which refers to an individual's propensity to accept and use new technologies for daily needs. A non-experimental quantitative research design with a descriptive method was employed. Data collection was conducted through an online questionnaire distributed to 100 senior high school teachers in Bandung City, Indonesia. The sampling technique used was non-probability sampling, specifically snowball sampling. The instrument utilized in this study was the Technology Readiness Index, which has a high reliability score. Data were analyzed using descriptive statistics, normality tests, and the Mann-Whitney and Kruskal-Wallis tests. The findings revealed that 52% of respondents fell into the high technology readiness category, indicating that proactive school management supports teachers in being more inclined to accept and use new technologies effectively. The study highlights the importance of school leadership in fostering a positive technological environment, with implications for future teacher training programs.